Adhesion Energy Modulation Acts as an NGF Receptor Activator for Neuronal Differentiation in NGF‐Free Medium. Issue 28 (4th September 2022) - Sénépart, Océane; Legay, Claire; Helary, Christophe; Hamraoui, Ahmed
Abstract: Neuronal repair is promoted after a nerve injury by chemical and physical stimuli from their environment. Among them, local adhesion energy gradients generated on surfaces trigger cone formation and neurite outgrowth without any nerve growth factor (NGF) addition. In this study, the molecular mechanisms leading to neuronal differentiation after stimulation via energy gradients are investigated. For this purpose, PC12 cells are cultured on n ‐[3‐(trimethoxysilyl)propyl] ethylendiamine (EDA) and n ‐hexyl trimethoxysilane (HTMS), two functionalized surfaces possessing local energy gradients but chemically different. These surfaces similarly trigger neurite and growth cone formation after 3 days in culture. Gene expression of PI3/Akt quantified through a microarray and the action of a specific inhibitor of the corresponding pathway reveal that PI3/Akt signaling pathway is induced and activated on these surfaces in the same way as NGF does after binding on its TrkA receptor. The biological downstream effectors of this signaling pathway are also upregulated, thereby promoting cell survival, growth cone formation, and neurite outgrowth. EDA and HTMS surfaces act as an ongoing stimulus of the TrkA receptor as the addition of 100 nM K252a, its specific inhibitor, leads to the inhibition of neurite growth. Taken together, these results suggest that functionalized surface with energy surface gradients could be useful to promote nerve repair after an injury. Abstract : The modulation of the adhesion energy induced by the functionalized surface activates the nerve growth factor (NGF) receptor as does the NGF added in the culture medium. Polymerase chain reaction analysis confirms this result. The aminosilane, n‐[3‐(trimethoxysilyl)propyl]ethylendiamine (C8H22N2O3Si; EDA)(R–NH2 ) and n‐Hexyltrimethoxysilane (HTMS)(R–CH3 ) surfaces act as a continuous stimulus of tropomyosin receptor kinase A (TrkA) that is the specific NGF receptor because of the addition of 100 nM of K252a, its specific inhibitor, leads to the inhibition of neurite growth.